User perception of energy consumption in two high-performance school buildings / Mohd Najib Mohd Salleh, Siti Rasidah Md Saki and Mohd Zin Kandar - Mohd Salleh, Mohd Najib; Md Saki, Siti Rasidah; Kandar, Mohd Zin (2018)
Today, environmental pollution is a significant challenge for the world. The need to find solutions in the construction sector has been developed. However, the resulting value is strongly influenced by environmental factors, location, and climate. Expected energy demand in 2030 will reach as much as 40% compared to 2007. Malaysia recorded a 31.2% increase in energy consumption for the years 2000 to 2010. Referring by World Markets Observatory (WEMO) on 2017 report shows the increasing by 4.8% on 2030 for Malaysia's energy usage (Yunus, 2017). To address the rising energy that directly affects the problems of urbanisation, and climate change, factor energy efficiency should be a critical action. The implementation of energy-efficiency policies can also improve the quality of life and reduce the impact of environmental pollution. One of the factors that significantly influence energy-efficiency in a building is user behaviour. According to Schipper and Meyers,a decision that made by human can affect energy consumption in a Building (Lutzenhiser, 1993). Thus, the key to the energy consumption pattern in the future is to understand and identify the practical methods for managing user. However, based on Ron Widman study, there are relatively few studies that are related to user behaviour and energy toward building an institution. While Power Save School Program expects a reduction of 5% to 15%,this can only be achieved by changingin user behaviour in school(Widman, Simmons, Kaplan, & Young, 1984). This study aimed to investigate the perception of a user to use energy in building two high-performing schools in Malaysia. 140 questionnaires were distributed to the two schools with 70 polls for each school. Respondents who were involved comprised of students and teachers with 86% of students and 14% of teachers. A survey conducted referring to the three top factors influencing energy efficiency in buildings, namely: 1) Building Design, 2) Services Design and 3) User Behavior. The results from the analysis conducted by three essential user perceptions; Perception of Building Design (PBD), Perception Services Design (PSD) and Perception User Behavior (PUB) haveshown there is a relationship. The study also illustratedthe monthly energy consumption data for three years until 2014. The floor area around the building has been used in deriving the energy index of the building.